Pengaruh Cash Position, Leverage, dan Firm Growth Terhadap Kebijakan Dividen - Teresia, Teresia; Santioso, Linda (Jurnal Paradigma Akuntansi, 2025)
This study aims to find out the role of cash position, leverage, and firm growth on dividend policy in listed consumer cyclical and non-cyclical companies listed on the Indonesia Stock Exchange in 2019-2021. Purposive sampling was used to select the sample, and valid data came from 23 different companies. Multiple regression analysis is used in the data processing technique, which is aided by the SPSS (Statistical Product and Service Solution) program V26.0 and Microsoft Excel 365 The results of this study indicate that cash position has a positive and significant effect on dividend policy, while leverage and firm growth have no effect on dividend policy. The implication of this research is comprehending the importance of cash position, leverage, and firm growth in dividend policy to give investors confidence to invest their funds or invest.